Accumulating puhunan: Disposable and superfluous affective capacities of life-making in the platform ELT economy - Imperial, Rowland (My University, 2025)
This paper attempts to re-conceptualize the role and circulation of affect in English language teaching (ELT) using Neferti X. M. Tadiar’s concept of life-times of disposability. I do this by drawing specifically on Tadiar’s notions of superfluity and disposability and then expanding these notions by drawing on the Tagalog notion of puhunan, which approximately translates to capital or investment in English. I relate the notion of puhunan to the ways in which the affective capacities and practices of life-making among language-minoritized, racialized, gendered, and sexualized ELT practitioners are not just circulated, but extracted, expropriated, disposed of, and wasted away for capital accumulation in the commercial education sector. My theory and analysis are contextualized at the intersection of the Philippines’ rapidly-growing, massive-scale platform economy and the booming transnational commercial online ELT industry in East and Southeast Asia. I explain how, for Filipino platform workers who take on precarious low-paying online ELT jobs, affect is vital for the accumulation of different forms of capital, such as puhunang sosyal (social capital, in Bourdieu’s sense of the term) and utang na loob (debt of gratitude or reciprocal obligation), both of which are crucial for accessing resources, work opportunities, and other forms of capital via labor-brokering ELT platforms. As disposable and superfluous human beings, Filipino platform ELT workers must rely ever increasingly on their own affective capacities and practices of life-making, instincts, and sensibilities to ensure not only the longevity and success of their profession, but also their survival.
PUBLISHED
Keywords: affect; affective labour; English language teaching; life-times of disposability; platform economy; Identities in Transformation; Inclusive Society; AFFECT; Affective labour; Applied Linguistics; LINGUISTICS; Platform economy; SOCIOLINGUISTICS; english language teaching; Education